Eficacia de la técnica Hall en dientes con hipomineralización incisivo molar - Acosta Otañez, Kayla Munay (2025)
This research aimed to identify the effectiveness of the Hall technique in teeth with molarincisor hypomineralization (MIH). The study is of a bibliographic and descriptive documentary nature, non-experimental, and of a transversal cut, based on articles published in the last 10 years, using databases such as PubMed, Google Scholar, and ProQuest. Twenty-eight articles were obtained through the PRISMA methodology, a globally accepted standard for scientific publications. After the bibliographic review, it was identified that the applied protocol is standardized, and therefore, the application of the Hall technique has demonstrated a large percentage of success both in teeth with MIH and caries, with a success rate of over 90%, as shown by Innes N et al. The criteria of minor and major failures, such as abscesses, loss of crowns, and the presence of new carious lesions around the margin of the crown, determined the clinical and radiographic characteristics. In conclusion, one of the best protocols applied is the one established by the author above, demonstrating a high percentage of success for being a minimal intervention technique.